2022
DOI: 10.3390/ijerph19074420
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Elemental Analysis of Human Optic Chiasm—A New Perspective to Reveal the Pathomechanism of Nerve Fibers’ Degeneration

Abstract: The effect of metals on the functioning of the human eye is multifactorial and includes enzyme activity modulation, trace metal metabolic pathways changes, and cytotoxic activity. Functional dysfunctions appear mostly as a result of the accumulation of toxic xenobiotic metals or disturbances of micronutrients’ homeostasis. So far, the affinity of selected metals to eye tissues, i.e., the cornea, choroid, lens, and anterior chamber fluid, has been most studied. However, it is known that many eye symptoms are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 73 publications
1
15
0
Order By: Relevance
“…There was also no significant correlation between brain and liver Al levels. A similar result was obtained in the previous study, which was a multi-element analysis of post-mortem tissue from the optic chiasm and optic nerves [33]. It should be noted that the presence and importance of Al in the brain is mainly analyzed in relation to neurological disorders, i.e., amyotrophic lateral sclerosis, senile dementia, Parkinson's disease, and, to some extent, Alzheimer's disease and autism spectrum disorder (ASD) [56][57][58].…”
Section: Xenobiotic Toxic Metalssupporting
confidence: 90%
See 2 more Smart Citations
“…There was also no significant correlation between brain and liver Al levels. A similar result was obtained in the previous study, which was a multi-element analysis of post-mortem tissue from the optic chiasm and optic nerves [33]. It should be noted that the presence and importance of Al in the brain is mainly analyzed in relation to neurological disorders, i.e., amyotrophic lateral sclerosis, senile dementia, Parkinson's disease, and, to some extent, Alzheimer's disease and autism spectrum disorder (ASD) [56][57][58].…”
Section: Xenobiotic Toxic Metalssupporting
confidence: 90%
“…The procedure of the human tissues pre-treatment was proposed previously [ 30 , 31 , 32 , 33 ]. In brief, wet mineralization of each 0.3–0.5 g sample was performed via the addition of 7 mL of 69% HNO 3 ultrapure for trace metal analysis (Baker, Radnor, PA, USA), followed by heating to 190 °C in closed Teflon containers in the microwave mineralization system Multiwave 5000 (Anton Paar, Graz, Austria).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample preparation procedure was the same as previously published [51][52][53]. In brief, 7 mL of 69% suprapur nitric acid HNO 3 (Baker, Radnor, PA, USA) was added to approximately 0.3-0.5 g of tissue sample, followed by heating to 190 • C in closed Teflon containers in the microwave mineralisation system Multiwave 5000 (Anton Paar, Graz, Austria).…”
Section: Sample Mineralisationmentioning
confidence: 99%
“…Another group showed that �tanium content in mouse hippocampus a�er 90 days of con�nuous intranasal exposure to TiO2 nanopar�cles was 0.6 mg/g �ssue at the highest administered dose of 10 mg/kg body weight (Ze et al, 2014), much higher than the levels observed in humans. Titanium can be found in human �ssue at lower average concentra�ons ranging from 1 μg/g (Peters et al, 2020) up to 80 μg/g (Baj et al, 2023) in the human brain. Thus, neuroinflamma�on and impairment of spa�al memory observed in mice occur at more than ten �mes higher brain content than observed in humans.…”
mentioning
confidence: 99%